Decoding of PDF417 barcode in Identity Authentication Based on LabVIEW - Qian Song; Li Liu (Institute of Advanced Engineering and Science, 2013)
Two dimensional barcode had widely applied in identity authentication. In this paper, the symbol structure of PDF417 barcode was introduced, and the image processing methods used in PDF417 barcode recognition were researched. A quick and effective method to calculate the width of the unit module in PDF417 barcode was proposed, and a recognition and decoding system of PDF417 barcode based on software development platform of the LabVIEW virtual instrument was designed and implemented. The system could process and analyze the images containing PDF417 barcode collected by camera in real time, and achieve the fast and omnibearing decoding of the barcode. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2607